A Rare De Novo Myoepithelial Carcinoma Ex Pleomorphic Adenoma in a Young Woman - Geeta Ahuja; Delaram J. Taghipour; Olubode A. Olufajo; Bonnie C. Davis; Babak Shokrani; William R. Bond (Case Reports in Otolaryngology)
Carcinoma ex pleomorphic adenoma, an uncommon neoplasm of the parotid gland, accounts for less than 4% of salivary gland tumors. It arises from a benign pleomorphic adenoma presenting in the sixth to eighth decades of life. We present this as a unique account of a primary parotid gland carcinoma, arising from myoepithelial cells, without a known precursor lesion, in a 28-year-old woman. This presentation seeks to provide familiarity of an unusual presentation of an unexpected rare pathology in a young female patient and the tools utilized for an accurate diagnosis.